The Prevalence of Traditional Cardiovascular Risk Factors in Low Socioeconomic Use individuals in Birjand 2008 (East IRAN) - Toba Kazemi; Mohamad Reza Rezvani; Gholam-Reza Sharifzadeh; Ali Sadri; Hamid Reza Mashraghi Moghaddam; Mahmood Hosseinzadeh Maleki (Journal of Cardio-Thoracic Medicine, 2015)
Introduction : Studying the prevalence of cardiovascular risk factors in low socioeconomic groups is of great importance. People who are under the supervisioin and care of Imam Khomeini Relief Foundation are the most deprived in Iran. The present survey aimed at investigating the prevalence of traditional cardiovascular risk factors among  the citizens who are under the supervision of Imam Khomeini Relief Foundation (IKRF). Mathrials and Methods: This cross-sectional  study was done on 1008 individuals protected by the IKRF in Birjand in 2008 through multi-stage, random sampling  Demographic were recorded. Furthermore, blood pressure, waist  circumference, weight  and height were measured by two trained nurses. Fasting Blood Sugar (FBS) and serum lipids were measured within 12 hours of overnight fasting. Chi-square and T-test were used for data analysis at the significant level of 0.05 using SPSS software (version 15). Results: The mean age of  the subjects was 39±16.8 years and the most common risk factor proved to be dyslipidemia (72%). The prevalence of hypercholesterolemia and hypertriglyceridemia was 43/2% and 12.7% respectively. Obesity was detected in 32.1% . The prevalence of hypertension (HTN) and diabetes mellitus (DM) appeared to be 13.1% and 6.3% respectively. Smoking was distinguished in 9.8 % of the participants. The prevalence of high Cholestrol (P=0.001),high LDL(p=0.01),low HDL(P